Pengaruh Pemberian Konseling Gizi Terhadap Asupan Zat Gizi Dan Kadar Glukosa Darah Pada Pasien Diabetes Mellitus Tipe 2 Di Wilayah Kerja Puskesmas Motoling - Ana B Montol; Jufri Sineke; Terema M.E. Kolompoy (Jurnal GIZIDO, 2018)
Diabetes Mellitus is a group of heterogeneous disorders characterized by elevated blood glucose levels or hyperglycemia. Counseling to people with Diabetes Mellitus about nutrition and healthy lifestyle is a method to raise awareness of Diabetes Mellitus patients to change food intake so as to improve blood glucose levels. The purpose of this study is to determine the effect of nutrition counseling on nutrient intake and blood glucose levels in patients with type 2 Diabetes Mellitus in the work area of ​​Motoling Puskesmas. The research type is pre experiment design with one group pretest and posttest approach. The population in this study were 55 outpatient Diabetes Mellitus patients at Motoling Puskesmas, a sample of 23 outpatient Diabetes Mellitus Type 2 patients at Motoling Puskesmas. Nutrition counseling using media leaflets is given four times a month. Data Food intake was taken by using food recall 24 hours, data of glucose level of patient was taken by doing autocheck blood sugar test and for characteristic data of respondent using questioner. To determine the difference of glucose level with carbohydrate and fat intake before and after nutritional counseling was analyzed by using paired test of T test and Wilcoxon test. The results showed that there was a significant difference between carbohydrate intake before and after nutritional counseling (p = 0.002 <α 0.05). Average carbohydrate intake before counseling 359.52 g and after counseling 290.09 g a decrease of 69.43 g. For fat intake showed no significant difference in carbohydrate intake before and after nutritional counseling (p = 0.009 <α 0.05). Average fat intake before counseling 128.61 g and after counseling 75.04 g decreased 53.56 g. While blood glucose levels showed no significant difference in carbohydrate intake before and after nutritional counseling (p = 0.000 <α 0.05). Mean blood glucose levels before counseling 255 mg / dl to 202.39 mg / dl decreased 52.60 mg / dl. Conclusion, there is a significant difference between nutrient intake and blood glucose levels in patients with Diabetes Mellitus type 2 in the work area of Motoling Puskesmas.